The Crucible of Francoism : Combat, Violence, and Ideology in the Spanish Civil War. - Alcalde, Ángel Alcald (Sussex studies in Spanish history., 2021)
The July 1936 coup d'tat against the Spanish Second Republic brought together a diversity of anti-Republican political and social groups under the leadership of rebel Africanista military officers. In the ensuing Civil War this coalition gradually came under the rule of Generalissimo Franco. This volume explores the hypothesis that the violence and combat experiences of the war were the fundamental ideological crucible for the Francoist regime. The rebels were a group of reactionary and anti-liberal forces with little ideological or political coherence, but they emerged from the conflict not only victorious but ideologically united under the dictator's power. Key to understanding this transition are the different political cultures of the rebel army, how the combatants' war experiences contributed to the transformation of diverse rebel groups, and the role of foreign armed intervention. The contributors examine not only the endogenous Spanish political and military cultures of the Francoist coalition, but also the transnational influence of foreign groups. The roots of Francoist political culture are found in the Falangist and Carlist militias, and Civil Guard units, that lent their support to the military rebellion. The war experiences of conscripts, colonial troops, and junior officers forged the Francoist ideology. It was reinforced by fascist influences and assistance from Germany and Italy, and the lesser-known contributions of Swiss and White Russian volunteers. At the beginning of the conflict the rebel side was not homogeneous. But it weaved together a complex, transnational web of political and military interests in the midst of a bloody and destructive war, transforming itself in the process to a political and dictatorial platform that was to rule Spain for many years.